O NÍVEL DE EVIDENCIAÇÃO DOS DERIVATIVOS FINACEIROS: UMA ANÁLISE DAS EMPRESAS BRASILEIRAS DO SETOR DE ENERGIA ELÉTRICA - Fernandes Martins, Vidigal; Prazeres Mendonça, Larissa (LINKSCIENCEPLACE, 2026)
The use of financial derivatives is becoming more frequent in national and international companies irrespective of the sector. The use of these instruments by companies which belong to the Brazilian Electric Power Sector is due to the complexity of their activities and the risks inherent in it, thus they are often used as a way to protect such risks. With the constant usage of derivatives, arises the need for an adequate disclosure by companies, with regard to information provided to the market. Considering this, the convergence to international standards may be determinant. Therefore, this study aimed to investigate how disclosure rates of financial derivatives in Brazilian Electric Power companies have behaved. For this purpose, it was considered CPC 40 (R1) – Instrumentos Financeiros: Evidenciação, and were quantified the disclosure rates of those companies in the years 2003, 2008 and 2013 based on specific items.